Normothermic Ex Vivo Perfusion Provides Superior Organ Preservation and Enables Viability Assessment of Hearts From DCD Donors. Issue 2 (February 2015) - Iyer, A.; Gao, L.; Doyle, A.; Rao, P.; Cropper, J. R.; Soto, C.; Dinale, A.; Kumarasinghe, G.; Jabbour, A.; Hicks, M.; Jansz, P. C.; Feneley, M. P.; et al.
<x xml:space="preserve">Abstract</x> The shortage of donors in cardiac transplantation may be alleviated by the use of allografts from donation after circulatory death (DCD) donors. We have previously shown that hearts exposed to 30 min warm ischemic time and then flushed with Celsior supplemented with agents that activate ischemic postconditioning pathways, show complete recovery on a blood‐perfused ex vivo working heart apparatus. In this study, these findings were assessed in a porcine orthotopic heart transplant model. DCD hearts were preserved with either normothermic ex vivo perfusion (NEVP) using a clinically approved device, or with standard cold storage (CS) for 4 h. Orthotopic transplantation into recipient animals was subsequently undertaken. Five of six hearts preserved with NEVP demonstrated favorable lactate profiles during NEVP and all five could be weaned off cardiopulmonary bypass posttransplant, compared with 0 of 3 hearts preserved with CS (p < 0.05, Fisher's exact test). In conclusion, DCD hearts flushed with supplemented Celsior solution and preserved with NEVP display viability before and after transplantation. Viability studies of human DCD hearts using NEVP are warranted.